Legal Issues Concerning Real Estate as Secured in Loan Contract: Comparative Study of Mortgage in Thailand and the Lao People’s Democratic Republic (in Thai) - ธรรมวงศ์, สุขภาวรรณ; ว่องวัฒนาภิกุล, ชลอ (Connexion: Journal of Humanities and Social Sciences, 2016)
This article aims to study the problems and obstacles in the provisions of the law on Secured Transaction 2005 Act in the Lao People's Democratic Republic (Lao PDR) in issues relating to the mean, scope of the mortgage, the rights and obligations of mortgagors and mortgagees by doing a comparative study on the civil and commercial code, chapter 3 of the 12 characteristics of mortgage in Thailand by researching documents related to doctrines, laws both in Thai and Lao languages in order to find conclusive analysis on the matter. According to a study the legal issues concerning real estate as secured load, confirmed that the law on Secured Transaction 2005 Act had not defined the scope of the mortgage. The law was not defined the rights of the mortgage as security for repayment, including what types of properties that can be mortgaged. The law did not state clearly about the rights and obligations of mortgagors and mortgagees and the mortgage of land be included the buildings or not as well as the rules of the mortgage and removing the mortgaged property out, which the law did not clearly define as well. With the unclear of the law, the law enforcement strongly impacts of fairness and public interest in Lao PDR. Therefore, it is expedient to amendment and revise the law on Secured Transaction 2005 Act, which clearly defines the scope of the mortgage, category the types of properties that can be mortgaged, the rights of mortgagors and mortgagees as well as the enforcement of the mortgage has to be more details and clarity like the Civil and Commercial Code Characteristics of Thai mortgage in order to make the more fair of the law enforcement on a mortgage in Lao PDR.